KNOWLEDGE POLICIES IN THE MODERN UNIVERSITY - Alexander A. Polonnikov (Moscow Polytechnic University, 2016)
The article explores the epistemological foundations of universities' educational practices. It is shown that each of these practices refers to a particular form of educational knowledge depending on the actual mode of such reference. The author comes to a conclusion that epistemological policies are linked to socio-cultural reproduction, rooted in the universities interest in preserving the existing form of educational knowledge.